1976
DOI: 10.1103/physrevlett.37.882
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a Narrow Antibaryon State at 2.26GeV/c2

Abstract: the situation of the Kerr black-hole uniqueness proofs, since in these proofs very strong symmetry requirements are made, which are inconsistent with the generic condition: The generators of the Kerr event horizon, for example, never feel tidal forces. However, the black-hole uniqueness theorems are frequently used to argue that the final black-hole state is of Kerr type; the symmetry requirements are then not expected to hold exactly for all time, just approximately in the limit of a long time after the black… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

1976
1976
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(36 citation statements)
references
References 14 publications
0
36
0
Order By: Relevance
“…Masses are obtained in the present study for each case of the model potential, ν= 0.5 to ν=2.0. Note that, A are masses without first order correction and B are masses with first order correction in Table [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. We plot graphs for calculated excited state (S and P state) with different potential index (M → ν) (See Fig.…”
Section: The Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Masses are obtained in the present study for each case of the model potential, ν= 0.5 to ν=2.0. Note that, A are masses without first order correction and B are masses with first order correction in Table [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. We plot graphs for calculated excited state (S and P state) with different potential index (M → ν) (See Fig.…”
Section: The Modelmentioning
confidence: 99%
“…Λ + c has been discovered at BNL [7] in 1975 . Shortly, Σ ++ c mass was discovered at FNAL [8] in 1976. Then Ξ c were announced by Belle [3] and also by BABAR collaboration [4].…”
mentioning
confidence: 99%
“…The lowest-lying charmed baryon Λ c was discovered more than 40 years ago [1], but its decays have not yet been fully mapped out due to the many available modes. Significant progress toward this goal has been made in the past few years, thanks to advances in particle identification, tracking, and collider luminosity.…”
Section: Introductionmentioning
confidence: 99%
“…Knapp et al (106) have reported observation of a sharp peak in the mass spectrum of An + n -rr -produced by photons interacting with beryllium. Some details ofthe experimental arrangement have been presented above in the discussion of IjJ production by this group at Fermilab.…”
Section: Baryonsmentioning
confidence: 98%